MPDNet: A Transformer-based real-time passenger detection network in metro stations - Yang, Jun; Gong, Mengjie; Dong, Xueru; Liang, Jiahua; Wang, Yan (Frontiers in Physics, 2022)
We propose a passenger flow detection method for dense areas of subway stations to address the current situation that existing pedestrian detection models cannot meet the real-time performance requirements in subway applications and lack validation in multiple subway scenarios. First, we designed the MPDNet model, which uses PVT-small to extract features and an improved feature pyramid network (FPN) for upsampling using the adaptively spatial feature fusion (ASFF) algorithm to retain more local information in the output of the FPN. Second, to better evaluate the performance of models in the metro, we collected subway surveillance video data and proposed the MetroStation dataset. Finally, we trained and evaluated the performance of the MPDNet model on the MetroStation dataset. We compare our method with several common object detection models on the MetroStation dataset, using mAP and frames per second (FPS) to verify its accuracy. The experiments on the MetroStation dataset demonstrated that the MPDNet performed well and satisfied inference speed requirements in metro passenger flow detection.